Presentation and Validation of a Model for Factors Affecting Marketing and Competitiveness in the Automotive Industry of Iran - Javadi, Iman; Khandan Alamdar, Saber; Ghazanfari, Hossein (Management Strategies and Engineering Sciences, 2023)
Competitiveness has been one of the critical topics emphasized in recent years in the literature on management and marketing. This study aims to identify, categorize, and model the factors influencing marketing and competitiveness in Iran's automotive industry using a qualitative thematic analysis approach. In this regard, interviews were conducted with 14 experts and senior specialists in the automotive marketing domain, each possessing at least 10 years of work experience and a minimum of a master's degree. Eleven key components were identified: the contexts included domestic and foreign investment attraction, proper policymaking, sanctions, government control, and monopolization. The processes identified were marketing and competitiveness in the automotive industry, knowledge and technology development, improvement of design and production processes, and enhancement of services. The outcomes of the proposed model included customer satisfaction and increased market share. In the quantitative phase, the model derived from the qualitative section was tested using structural equation modeling based on data collected from 373 questionnaires. The results indicated that domestic and foreign investment attraction, proper policymaking, monopolization, and sanctions significantly impact marketing and competitiveness in the automotive industry, knowledge and technology development, improvement of design and production processes, and enhancement of services. Additionally, government control significantly influences marketing and competitiveness in the automotive industry, knowledge and technology development, and improvement of design and production processes. Furthermore, marketing and competitiveness in the automotive industry, knowledge and technology development, improvement of design and production processes, and enhancement of services significantly impact customer satisfaction and increased market share. However, the influence of government control on service enhancement was not confirmed.